The life & death of Peter Sellers [videorecording (DVD)] - Hopkins, Stephen, 1959-; Rush, Geoffrey, 1951-; Watson, Emily, 1967-; Lithgow, John, 1945-; Theron, Charlize (HBO Home Entertainment, 2012)
A kaleidoscopic look inside the unquiet mind of Peter Sellers. Despite his Hollywood success, his comic virtuosity belied a troubled private life plagued by self-loathing, insecurity, and abusive behavior. The film peers behind the many faces of Peter Sellers to reveal how the comic genius teetered on the edge of madness.